Analisis Kebijakan Penyelenggaraan Pendidikan Inklusif di Provinsi Jakarta - Kamal Fuadi (Hikmah: Journal of Islamic Studies, 2015)
Abstract This research uses descriptive-qualitative method to describe policy of inclusive educational implementation and policy implementation in Province of Jakarta. Based on finding of the research, some conclusions can be made as follow: first, inclusive education held in Province of Jakarta tends to describe unification of disorder children into school program. Though some students with special intelligence and skill are included in the inclusive education, their existence is not become the very issue in inclusive educational implementation. Second, the inclusive educational implementation does not use a model as instructed in some literatures and common rules of inclusif education. The model is just a part of strategies that teachers need to understand and execute. Third, some kategories of disorder children are still excluded from inclusive educational program. The cause is inadequacy of school resourches for it. Fourth, the number of school for implementing inclusive education in Province of Jakarta exceed what given by central government. Fifth, Province Government of Jakarta always cooperates with schools to facilitate training for inclusive teachers, to give financial aid, tools and infrastructure aid, and scholarship for schools which implement the inclusive education. Keywords: Policy, Inclusive Educational Abstrak Penelitian ini menggunakan metode kualitatif deskriptif dalam upaya mendeskripsikan kebijakan penyelenggaraan pendidikan inklusif dan implementasi kebijakan di Provinsi DKI Jakarta. Berdasarkan hasil penelitian ditemukan bahwa, pertama, pendidikan inklusif yang diselenggarakan di Provinsi DKI Jakarta cenderung untuk mendeskripsikan penyatuan anak-anak berkelainan (penyandang hambatan/cacat) ke dalam program sekolah. Walaupun peserta didik dengan kecerdasan dan/atau bakat istimewa juga dimasukkan dalam salah satu peserta didik pendidikan inklusif, keberadaan mereka tidak banyak menjadi isu dalam penyelenggaraan pendidikan inklusif. Kedua, penyelenggaraan pendidikan inklusif tidak menggunakan model sebagaimana terdapat dalam literatur dan ketentuan umum pendidikan inklusif. Model hanya merupakan bagian dari strategi yang perlu diketahui dan dilaksanakan guru. Ketiga, belum semua kategori anak berkebutuhan khusus diterima menjadi peserta didik program pendidikan inklusif. Hal tersebut berkaitan dengan belum terpenuhinya sumber daya sekolah yang memadai. Keempat, penunjukkan sekolah-sekolah penyelenggara pendidikan inklusif di Provinsi DKI Jakarta melebihi ketentuan yang ditetapkan pemerintah pusat. Kelima, Pemerintah Provinsi DKI selalu bekerja sama dengan pihak sekolah dengan memberikan pelatihan bagi guru-guru inklusi, bantuan finansial, bantuan sarana dan prasarana, dan beasiswa bagi sekolah-sekolah penyelenggara pendidikan inklusif. Kata Kunci: Kebijakan, Pendidikan Inklusif